Pengaruh Kejenuhan Kerja (Burnout) Terhadap Kinerja Karyawan Bagian Operator Di PT PLN (Persero) Unit Pelaksana Pengendalian Pembangkit Jambi Unit Layanan Pusat Listrik Payo Selincah - Said Almaududi (Ekonomis: Journal of Economics and Business, 2019)
Excessive and prolonged work stress can cause depression and if not immediately addressed can cause employees to experience burnout syndrome, an emotional condition where an employee feels tired and bored both physically and mentally. On the other side it can be seen that the performance at PLN Persero Company has not been said to be optimal because it is unable to handle public complaints effectively and efficiently. The research aims to find out how the influence of burnout on the performance of the operator's employees in PLN Persero Company Jambi Power Plants Control Unit Payo Selincah Central of Electric Service Unit as well as how much influence the burnout on the performance of the operator employee employees at PLN Persero Company Jambi Power Plants Control Unit Payo Selincah Central of Electric Service Unit. The research method used is a descriptive quantitative method with burnout and the dependent variable is performance. The analytical tool used is simple linear regressionanalysis, correlationanalysis, coefficient of determination analysis and statistical test t analysis. The object of this research is the operator part of employees PLN Persero Company Jambi Power Plants Control Unit Payo Selincah Central of Electric Service Unit. Based on the results of simple linear regression analysis, showing the equation Y = 36,545 + 0,546 with a correlation of 0,542 or 54,2%. Determination value of 0,294 or 29,4% which means that the influence of burnout on performance is 29,4%, while 70,6% is influenced by other variables not examined in this study. T test value of 3,974 with a significance value of 0,00<0,05 which is greater than the ttable value of 2,02439. This research is to show that the level of burnout and the performance of the operator's employees in PLN Persero Company Jambi Power Plants Control Unit Payo Selincah Central of Electric Service Unit is high. And burnout also affects the performance of the operator's employees in the PLN Persero Company Jambi Power Plants Control Unit Payo Selincah Central of Electric Service Unit.